Coordination and Return Uncertainties in Closed Loop Supply Chains - Sepulveda-Rojas, J (Institute of Electrical and Electronics Engineers Inc., 2016)
In this article we analyze quantitatively the gains of coordination in a closed loop supply chain context for different levels of uncertainty about returns. The novel characteristic of this study is to evaluate quantitatively the value of coordination for operational decisions (in the context of inventory management decisions). Thus, we find it interesting to verify its validity in the reverse logistics setting. We observe principally that the works in this area, according to some authors, use approaches such as game theory or contracting. This leads us to believe that there is a gap in the studies on the influence of coordination in relation to operational decisions such as inventory management. One of the more important characteristics of the closed loop supply chain context is the addition of uncertainties about returns. This heightens our interests on the analysis of this topic. We show through a numerical experiment the convenience of global coordination in a closed loop supply chain for different levels of uncertainty. Finally, we observe that the value of coordination, as uncertainty increases, slightly decreases. © 2016 IEEE.